A smoking prevention photoageing intervention for secondary schools in Brazil delivered by medical students: protocol for a randomised trial - Faria, Bianca Lisa; Klode, Joachim; Schadendorf, Dirk; Brinker, Titus Josef (BMJ open, 2017)
INTRODUCTION: Most smokers start smoking during their early adolescence, often with the idea that smoking is glamorous; the dramatic health consequences are too far in the future to fathom. We recently designed and tested an intervention that takes advantage of the broad availability of mobile phones as well as adolescents' interest in their appearance. A free photoageing mobile app (Smokerface) was implemented by medical students in secondary schools via a novel method called mirroring. The pupils' altered three-dimensional selfies on tablets were 'mirrored' via a projector in front of their whole grade. This is the first randomised trial to measure the effectiveness of the mirroring approach on smoking behaviour in secondary schools. METHODS AND ANALYSIS: The mirroring intervention, which lasts 45 min, is implemented by Brazilian medical students in at least 35 secondary school classes with 21 participants each (at least 35 classes with 21 participants for control) in February 2018 in the city of Itauna, Brazil. External block randomisation via computer is performed on the class level with a 1:1 allocation. In addition to sociodemographic data, smoking behaviour is measured via a paper-pencil questionnaire before, 3 and 6 months postintervention plus a random carbon monoxide breathing test at baseline and end line. The primary outcome is cigarette smoking in the past week at 6 months follow-up. Smoking behaviour (smoking onset, quitting) and effects on the different genders are studied as secondary outcomes. Analysis is by intention to treat. ETHICS AND DISSEMINATION: Ethical approval is obtained from the ethics committee of the University of Itauna in Brazil. Results will be disseminated at conferences, in peer-reviewed journals, throughout the Education Against Tobacco network social media channels and on our websites.